Gut Microbiome and Metabolome Were Altered and Strongly Associated With Platelet Count in Adult Patients With Primary Immune Thrombocytopenia - Zhang, Xuewu; Gu, Silan; You, Liangshun; Xu, Yu; Zhou, De; Chen, Yunbo; Yan, Ren; Jiang, Huiyong; Li, Yating; Lv, Longxian; Qian, Wenbin (Frontiers in Microbiology, 2020)
Gut microbiota has been implicated in the pathogenesis of many autoimmune diseases. This is still an area of active research given that the role of gut microbiota on the primary immune thrombocytopenia (ITP) remains unclear. In this study, fecal samples of 30 untreated adult primary ITP patients and 29 healthy controls (HCs) were used to investigate the gut microbial community and metabolite profiles. Our results show that fecal bacteria such as Blautia, Streptococcus and Lactobacillus are enriched, whereas bacteria such as Bacteroides are depleted in ITP patients. Notably, fecal metabolites such as fatty acyls and glycerophospholipids are enriched and strongly correlate with discrepant gut microbiota. Furthermore, combinations of Weissella and Streptococcus anginosus, or Cer (t18:0/16:0), Cer (d18:1/17:0) and 13-hydroxyoctadecanoic acid could provide good diagnostic markers for ITP. Moreover, a strong negative correlation was found between platelet count and altered gut microbiota such as Streptococcus anginosusand gut metabolites such as Cer (t18:0/16:0) in ITP. In conclusion, dysbiosis of both gut microbiota and metabolome develops in ITP patients compared to HCs. Several ITP-altered gut bacteria and metabolites can be diagnostic biomarkers for ITP, and are highly correlated with platelet count, suggesting that they may also play a role in ITP pathogenesis.